Environmental protection of Nb/Nb5Si3-based alloys by E/TBC systems. (February 2018) - Braun, Reinhold; Schulz, Uwe; Portebois, Léo; Mathieu, Stéphane; Vilasi, Michel; Drawin, Stefan
Abstract: Environmental/thermal barrier coatings (E/TBCs) were applied on an Nb/Nb5 Si3 -based alloy. The substrate material with the nominal composition Nb-23Ti-4Hf-3Cr-6Al-20Si (at.%) was manufactured by plasma melting. Rectangular platelets of this alloy were coated with chromia-silica forming M7 Si6 -based (M = Ti, Nb, Cr, X with X = Ni, Co, Fe) bond coats produced by pack cementation. The Co- and Fe-modified M7 Si6 -based layers also contained boron. On these grit blasted bond coats, ceramic topcoats of 7 wt.% yttria partially stabilised zirconia (YSZ) and gadolinium zirconate (GZO) were deposited using electron-beam physical vapour deposition. The E/TBC systems were thermally cycled at 1100 °C and 1200 °C in laboratory air (1 h at high temperature, 10 min at ambient temperature). Cross-sectional examinations of the samples after cyclic testing were carried out using scanning electron microscopy to study the protection capability of the E/TBC systems and failure mechanisms. The lifetimes of the E/TBC systems exceeded the maximum exposure period of 1000 cycles at 1100 °C. When cyclically tested at 1200 °C, the samples with Ni-modified and boron containing Co-modified M7 Si6 -based bond coats failed within 700 cycles. Failure was caused by spallation of thick oxides scales thermally grown on the substrate after degradation of the bond coats. The E/TBC systems with boron containing Fe-modified M7 Si6 -based bond coats exhibited lifetimes approaching 1000 cycles at 1200 °C. For both YSZ and GZO topcoats, chemical reactions with the TGOs were observed. Highlights: YSZ and GZO topcoats were deposited on an Nb-silicide based alloy using EB-PVD. Ni- and boron containing Co- and Fe-modified M7 Si6 -based bond coats were used. Lifetimes exceeding 1000 cycles were determined for the E/TBC systems at 1100 °C. Lifetime of E/TBCs with the Fe-modified bond coat approached 1000 cycles at 1200 °C. Both ceramic topcoats reacted with the oxide scales formed on the bond coats.